Effect of distance of vertical barrier wall to the release nozzle on the hydrogen concentration profile induced by impingement of unignited release of cryogenic hydrogen. (15th June 2023) - Gong, Liang; Han, Yifei; Zheng, Xianwen; Mo, Tianyu; Wang, Haoyu; Yao, Yongzheng; Zhang, Yuchun
Highlights: The maximum hydrogen concentration increases as the distance of the vertical barrier wall decreases. The inverse maximum hydrogen concentration increases linearly with the scaled distance. The hydrogen concentration in the horizontal and vertical direction increases as the distance of vertical barrier wall decreases. The hydrogen concentration in the horizontal and vertical direction follow Gaussian and exponential distribution, respectively. Abstract: As a recognized clean energy source with advantages of non-pollution, high energy density and less energy loss during the cooling process, cryogenic hydrogen is widely used worldwide. The barrier wall is an effective means of preventing the backward diffusion of jets. However, the effect of distance of vertical barrier wall to the release nozzle on the hydrogen concentration profile is still unknown. In this work, cryogenic hydrogen is released with different distances of the barrier wall (0.20, 0.25, 0.30, 0.35, 0.40 m) and temperatures of cryogenic hydrogen (140, 180, 220, 260, 300 K) experimentally. 10 hydrogen concentration sensors are placed in the horizontal and vertical directions on the barrier wall, respectively, to record the hydrogen concentration. It is found that the maximum hydrogen concentration increases as the distance of the vertical barrier wall decreases. Models of the maximum hydrogen concentration in volume and mass fraction are proposed. The hydrogen concentration increases significantly in the horizontal and vertical directions as the vertical barrier wall is placed closer to the release nozzle. The hydrogen concentration in the horizontal and vertical directions of the vertical barrier wall follows the Gaussian and exponential distribution, respectively. The prediction models of hydrogen concentration in the horizontal and vertical directions are proposed as well. The research results can provide a theoretical basis and data support for the design of safety codes for cryogenic hydrogen storage and the safety distance of barrier walls in hydrogen refueling stations.